2012
DOI: 10.1123/apaq.29.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Parent Perceptions of Factors Influencing After-School Physical Activity of Children with Autism Spectrum Disorders

Abstract: The study assessed parental perceptions of the benefits of physical activity (PA) and the factors that influence participation of children with autism spectrum disorders in PA after school. Data were collected from 103 parents using an online open-ended questionnaire and focus-group interviews. Data were analyzed using a socioecological model. Parents provided 225 responses that were coded as advantages, 106 as disadvantages, 225 as facilitators, and 250 as barriers of PA. The most frequently reported advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 32 publications
(60 reference statements)
6
91
0
2
Order By: Relevance
“…Following up the study on children's perceived barriers, Obrusnikova and Miccinello (2012) further explored what barriers to physical activity parents perceived their children with ASD to be experiencing. Again using the Social Ecological Model, the authors reported that the most common interpersonal barriers included parental lack of time or energy, and that their child did not have an exercise partner.…”
Section: Barriers To Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Following up the study on children's perceived barriers, Obrusnikova and Miccinello (2012) further explored what barriers to physical activity parents perceived their children with ASD to be experiencing. Again using the Social Ecological Model, the authors reported that the most common interpersonal barriers included parental lack of time or energy, and that their child did not have an exercise partner.…”
Section: Barriers To Physical Activitymentioning
confidence: 99%
“…In order to overcome the challenges associated with teaching PE to children with ASD, Several studies have found that children with ASD do not enjoy physical activities and would prefer more sedentary activities such as videogame or computer use (Obrusnikova & Cavalier, 2011;Obrusnikova & Miccinello, 2012). Because most PE classes follow a specific curriculum, teachers are encouraged to offer choices of physical activities to children with ASD as much as possible (Crollick, Mancil, & Stopka, 2006) to enhance participation.…”
Section: Teaching Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In looking at more specific responses, parents of children who gained more from the intervention discussed more formal aspects of "time", such as scheduling. This finding reiterates the barriers found by Obrusnikova and Miccinello (2012) in their study of the barriers to and facilitators of after-school activity for children with ASD. It is likely that when a high level of barriers is reported, parents would be more focused on more traditional services for children with ASD, which may limit the ability to ensure time for physical activity.…”
Section: Interaction Of Motor Skill Changes In Child's Lifementioning
confidence: 45%
“…Because of their proximity to the individual, parents are often used in research that seeks to gain insight about the effectiveness of programs for children with disabilities (Columna et al, 2008;Na, 2015;Obrusnikova & Miccinello, 2012). Furthermore, parents provide opportunities to see what is happening to the individual with a disability outside the context of many programs or interventions.…”
Section: Participants -Interview Sample (Qual)mentioning
confidence: 99%